2017
DOI: 10.1111/anec.12436
|View full text |Cite
|
Sign up to set email alerts
|

Novel method to assess intrinsic heart rate recovery in ambulatory ECG recordings tracks cardioprotective effects of chronic autonomic regulation therapy in patients enrolled in the ANTHEMHF study

Abstract: BackgroundPostexercise heart rate recovery (HRR) is a powerful and independent predictor of mortality. Autonomic regulation therapy (ART) with chronic vagus nerve stimulation (VNS) has been shown to improve ventricular function in patients with chronic heart failure. However, the effect of ART on HRR in patients with heart failure remains unknown.MethodsA new measure involving quantification of intrinsic HRR was developed for 24‐hr ambulatory ECG (AECG) recordings based on spontaneous heart rate changes observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In our previous work, we demonstrated that cardiopulmonary parameters decline more slowly in patients with IHD, indicating that repayment of the O 2 debt is prolonged in these patients in parallel with the delayed recovery of energy stores in skeletal muscle, which had strong prognostic power 25. The HRR-1 was found to have an immense prognostic power in patients with IHD 18–20. Several studies reported prolonged kinetics of V˙ o 2 or V˙ co 2 during recovery from maximal exercise in patients with HF, which was explained by impairment of the circulatory response to exercise and delayed recovery of cardiac output after exercise 24,41.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In our previous work, we demonstrated that cardiopulmonary parameters decline more slowly in patients with IHD, indicating that repayment of the O 2 debt is prolonged in these patients in parallel with the delayed recovery of energy stores in skeletal muscle, which had strong prognostic power 25. The HRR-1 was found to have an immense prognostic power in patients with IHD 18–20. Several studies reported prolonged kinetics of V˙ o 2 or V˙ co 2 during recovery from maximal exercise in patients with HF, which was explained by impairment of the circulatory response to exercise and delayed recovery of cardiac output after exercise 24,41.…”
Section: Discussionmentioning
confidence: 94%
“…25 The HRR-1 was found to have an immense prognostic power in patients with IHD. [18][19][20] Several studies reported prolonged kinetics of V . o 2 or V .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations